2007
DOI: 10.1111/j.1365-246x.2007.03333.x
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of scale lengths in stochastic fields and their seismic response: a quantification exercise

Abstract: S U M M A R YThe possibility that parts of the Earth's continental lower crust can be described with stochastic geological models has been suggested for some time. Recent studies of deeper well logs also indicate a possible stochastic structure at mid-crustal levels. This motivates a closer examination of the relation between the statistics of reflection wavefields and that of the lower crust. Such a relation can put important constraints on possible lower crustal models. This study follows up earlier efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Our numerical tests also confirm the analytical finding that the second-order statistics of a seismic or GPR reflection image should be sensitive to the power spectral slope of the velocity heterogeneity. However, the available empirical evidence regarding this result is still too thin and inconsistent to either corroborate or challenge it [e.g., Carpentier and Roy-Chowdhury, 2007;Scholer et al, 2010]. We therefore see this as an important topic for future research.…”
Section: Numerical Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our numerical tests also confirm the analytical finding that the second-order statistics of a seismic or GPR reflection image should be sensitive to the power spectral slope of the velocity heterogeneity. However, the available empirical evidence regarding this result is still too thin and inconsistent to either corroborate or challenge it [e.g., Carpentier and Roy-Chowdhury, 2007;Scholer et al, 2010]. We therefore see this as an important topic for future research.…”
Section: Numerical Verificationmentioning
confidence: 99%
“…This means that we estimate parameters describing the geostatistical nature of the heterogeneity, rather than a detailed distribution of material properties. To this end, estimation of the geostatistical properties of subsurface velocity heterogeneity from surface-based seismic and ground-penetrating radar (GPR) reflection images has been a long-standing problem of significant interest [e.g., Holliger et al, 1992;Hurich, 1996;Pullammanappallil et al, 1997;Rea and Knight, 1998;Bean et al, 1999;Poppeliers and Levander, 2004;Carpentier and Roy-Chowdhury, 2007;Knight et al, 2007]. Of particular interest has been the estimation of the lateral statistics of a subsurface velocity field from those of the corresponding reflection image, as this information cannot be obtained from borehole log or core analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Holliger et al [1994] and Pullammanappallil et al [1997] initially suggested that the average lateral correlation structures of both of these fields should be equivalent. However, the more recent results of Bean et al [1999] and Carpentier and Roy-Chowdhury [2007] have pointed out the fundamental dependence of the lateral correlation properties of a seismic image on bandwidth and on the vertical derivative operator that acts to create reflection coefficients from an impedance field, respectively. Clearly, such details concerning the physics of the experiment must be considered in any strategy to estimate the correlation structure of subsurface velocity from seismic reflection data.…”
Section: Introductionmentioning
confidence: 99%
“…[3] A number of studies have explored the relationship between the lateral correlation structure of seismic and radar velocity fields and those of the corresponding seismic and GPR reflection data [e.g., Gibson, 1991;Hurich, 1996;Pullammanappallil et al, 1997;Line et al, 1998;Rea and Knight, 1998;Bean et al, 1999;Knight et al, 2004;Oldenborger et al, 2004;Dafflon et al, 2006;Carpentier and Roy-Chowdhury, 2007;Knight et al, 2007]. Although the seismic and GPR communities have to date worked largely independently of one another, it is important to note that the results obtained are mutually transferrable because of the strong mathematical analogies that exist between seismic and electromagnetic wave propagation [e.g., Carcione and Cavallini, 1995;Belina et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…This method of statistically analyzing the reflection field of seismic data has been used extensively to study complex acoustic impedance variability in the solid earth (e.g. Goff et al, 1994;Holliger et al, 1994;Hurich and Kocurko, 2000;Carpentier and Roy-Chowdhury, 2007) even in areas where there is a predominance of diffuse reflectivity (as opposed to specular reflectivity) observed. This research represents the first application of Stochastic Heterogeneity Mapping to the ocean.…”
Section: Introductionmentioning
confidence: 99%